2006
DOI: 10.1016/j.chemosphere.2006.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi can alleviate the adverse effects of chlorothalonil on Oryza sativa L.

Abstract: A glasshouse pot experiment was conducted to investigate the effect of the fungicide chlorothalonil on the growth of upland rice, in the absence or presence of the arbuscular mycorrhizal fungus (AMF) Glomus mosseae (NM and GM treatments). The plants were grown with three concentrations of chlorothalonil (0, 50 and 100 mg kg À1 soil). Mycorrhizal colonization decreased significantly with increasing chlorothalonil concentrations. Plant biomass decreases were smaller in GM plants than in non-mycorrhizal (NM) plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Although some recent studies have shown that several plants can tolerate and detoxify Cd, few studies have examined the effects of soil microbes that form associations with these plants, especially arbuscular mycorrhizal (AM) fungi. AM fungi play significant roles in the recycling of plant nutrients, maintenance of soil structure, detoxification of noxious chemicals, control of plant pests, and regulation of plant growth and its interactions with the soil environment [9] , [10] . Plant-microbe symbioses are ubiquitous in both natural and most anthropogenically influenced soils [11] [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Although some recent studies have shown that several plants can tolerate and detoxify Cd, few studies have examined the effects of soil microbes that form associations with these plants, especially arbuscular mycorrhizal (AM) fungi. AM fungi play significant roles in the recycling of plant nutrients, maintenance of soil structure, detoxification of noxious chemicals, control of plant pests, and regulation of plant growth and its interactions with the soil environment [9] , [10] . Plant-microbe symbioses are ubiquitous in both natural and most anthropogenically influenced soils [11] [13] .…”
Section: Introductionmentioning
confidence: 99%
“…As observed, the colonization percentage was significantly decreased by the chlorothalonil application; however, there were no differences in root colonization percentage between the single dose and the two mycorrhizal doses, in neither fungicide treated nor untreated plant seeds. The concentration of chlorothalonil fungicide may also affect the symbiosis whith the host plant and decreased the colonization ratios [17].…”
Section: Resultads and Discussionmentioning
confidence: 99%
“…Inoculation of upland rice (Oryza sativa) with Glomus mosseae reduced the activity of the enzymes ascorbate peroxidase, catalase and peroxidase, and alleviated the adverse effects of chlorothalonil on growth [210]. The activity of phosphatase and urease in soils was stimulated by inoculation of Elsholtzia splendens and Zea mays with G. caledonium and G. margarita [211], and also Trifolium pratense with G. mosseae [212,213].…”
Section: Alteration Of Enzymatic Activities In Am-inoculated Plantsmentioning
confidence: 99%